Chronic loss of inhibitor-1 diminishes cardiac RyR2 phosphorylation despite exaggerated CaMKII activity - Neef, Stefan; Dewenter, Matthias; Saadatmand, Ali R.; Backs, Johannes (Naunyn-Schmiedeberg's archives of pharmacology, 2017)
Inhibitor-1 (I-1) modulates protein phosphatase 1 (PP1) activity and thereby counteracts the phosphorylation by kinases. I-1 is downregulated and deactivated in failing hearts, but whether its role is beneficial or detrimental remains controversial, and opposing therapeutic strategies have been proposed. Overactivity of Ca2+/calmodulin-dependent protein kinase II (CaMKII) with hyperphosphorylation of ryanodine receptors (RyR2) at the CaMKII-site is recognized to be central for heart failure and arrhythmias. Using an I-1-deficient mouse line as well as transfected cell lines, we investigated the effects of acute and chronic modulation of I-1 on CaMKII activity and RyR2 phosphorylation. We demonstrate that I-1 acutely modulates CaMKII by regulating PP1 activity. However, while ablation of I-1 should thus limit CaMKII-activation, we unexpectedly found exaggerated CaMKII-activation under β-adrenergic stress upon chronic loss of I-1 in knockout mice. We unraveled that this is due to chronic upregulation of the exchange protein activated by cAMP (EPAC) leading to augmented CaMKII activation, and using computational modeling validated that an increase in EPAC expression can indeed explain our experimental findings. Interestingly, at the level of RyR2, the increase in PP1 activity more than outweighed the increase in CaMKII activity, resulting in reduced RyR phosphorylation at Ser-2814. Exaggerated CaMKII activation due to counterregulatory mechanisms upon loss of I-1 is an important caveat with respect to suggested therapeutic I-1-inhibition, as CaMKII overactivity has been heavily implicated in several cardiac pathologies.